![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(2y-1\right)^{1000}-\left(3+y\right)^{1000}=0\)
\(\Rightarrow\left(2y-1\right)^{1000}=\left(3+y\right)^{1000}\)
\(\Rightarrow2y-1=3+y\)
\(2y-y=3+1\)
\(y=4\)
b) \(\left(x-\frac{2}{9}\right)^3=\left(\frac{2}{3}\right)^6\)
\(\left(x-\frac{2}{9}\right)^3=\left(\left(\frac{2}{3}\right)^2\right)^3\)
\(\Rightarrow x-\frac{2}{9}=\left(\frac{2}{3}\right)^2\)
\(x-\frac{2}{9}=\frac{4}{9}\)
\(x=\frac{2}{3}\)
c) \(\left(2x-1\right)^6=\left(2x-1\right)^8\)
\(\left(\left(2x-1\right)^3\right)^2=\left(\left(2x-1\right)^4\right)^2\)
\(\Rightarrow\left(2x-1\right)^3=\left(2x-1\right)^4\)
\(8x^3-1=16x^4-1\)
\(16x^4-8x^3=0\)
\(8x^3\left(2x-1\right)=0\)
Nếu \(8x^3=0\) thì \(x^3=0\Rightarrow x=0\)
Nếu \(2x-1=0\)thì \(2x=1\Rightarrow x=\frac{1}{2}\)
Vậy x=0 và x=1/2
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(\frac{x-y}{3}=\frac{2x+y}{8}=\frac{\left(2x+y\right)-\left(x-y\right)}{8-3}=\frac{x+2y}{5}=\frac{x+2y}{x}\)
\(\Rightarrow x=5\)
Thay \(x=5\)vào biểu thức \(\frac{x-y}{3}=\frac{x+2y}{x}\)ta được
\(\frac{5-y}{3}=\frac{5+2y}{5}\)
\(\Rightarrow5\left(5-y\right)=3\left(5+2y\right)\)
\(\Rightarrow25-5y=15+6y\)
\(\Rightarrow5y+6y=25-15\)
\(\Rightarrow11y=10\)\(\Rightarrow y=\frac{10}{11}\)
Vậy \(x=5\)và \(y=\frac{10}{11}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
ta có (2x-1)2+ /2y-x/ = 0
suy ra (2x-1)2 = 0 và /2y-x/ =0
2x-1 = 0 2y-x =0
2x = 0+1=1 2y-1/2=0
x = 1/2 2y = 0+1/2=1/2
y = 1/2 /2
y =1/4
Ta có::
(2x−8)2≥0∀x|x−2y|≥0∀x,y}(2x−8)2≥0∀x|x−2y|≥0∀x,y}⇒(2x−8)2+|x−2y|≥0∀x,y⇒(2x-8)2+|x-2y|≥0∀x,y
Mà (2x−8)2+|x−2y|=0(2x-8)2+|x-2y|=0
Dấu "==" xảy ra khi::
{(2x−8)2=0|x−2y|=0{(2x−8)2=0|x−2y|=0
⇒⇒{2x−8=0x−2y=0{2x−8=0x−2y=0
⇒⇒{2x=82y=x{2x=82y=x
⇒⇒{x=42y=4{x=42y=4
⇒⇒{x=4y=2{x=4y=2
Vậy x=4;y=2